Post-transfer editing in vitro and in vivo by the β subunit of phenylalanyl-tRNA synthetase - Roy, Hervé (Nature Publishing Group, 2004)
Translation of the genetic code requires attachment of tRNAs to their cognate amino acids. Errors during amino-acid activation and tRNA esterification are corrected by aminoacyl-tRNA synthetase-catalyzed editing reactions, as extensively described for aliphatic amino acids. The contribution of editing to aromatic amino-acid discrimination is less well understood. We show that phenylalanyl-tRNA synthetase misactivates tyrosine and that it subsequently corrects such errors through hydrolysis of tyrosyl-adenylate and Tyr-tRNA(Phe). Structural modeling combined with an in vivo genetic screen identified the editing site in the B3/B4 domain of the β subunit, 40 Å from the active site in the α subunit. Replacements of residues within the editing site had no effect on Phe-tRNA(Phe) synthesis, but abolished hydrolysis of Tyr-tRNA(Phe) in vitro. Expression of the corresponding mutants in Escherichia coli significantly slowed growth, and changed the activity of a recoded β-galactosidase variant by misincorporating tyrosine in place of phenylalanine. This loss in aromatic amino-acid discrimination in vivo revealed that editing by phenylalanyl-tRNA synthetase is essential for faithful translation of the genetic code.